(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This article examines the scientific activities of Sayyid Sharif Jurjani (1340–1413) during his residence in Samarkand under the patronage of Amir Timur and analyzes his contribution to the intellectual development of the Timurid era. The study highlights Amir Timur’s policy of gathering distinguished scholars from different regions of the Islamic world and transforming Samarkand into a major center of learning. Special attention is given to Jurjani’s arrival in Samarkand, his scholarly relationship with Amir Timur, and his famous intellectual debates with Sa’duddin Taftazani, which significantly influenced the development of Islamic theology, logic, and philosophy. The article also explores Jurjani’s role as a leading teacher in Timurid madrasas and examines the influence he exerted on a generation of prominent scholars, including Qadizada Rumi, Fathullah Shirvani, Ibn Arabshah, and others. Furthermore, the research discusses the dissemination of Jurjani’s works throughout the Islamic world and their enduring place in the educational curriculum of madrasas. The findings demonstrate that Jurjani’s nearly two decades of scholarly activity in Samarkand played a crucial role in strengthening the city’s status as a center of theoretical sciences and contributed significantly to the intellectual legacy of the Timurid Renaissance.